PENGELOLAAN PERIKANAN TONDA DENGAN RUMPON MELALUI PENDEKATAN SOFT SYSTEM METHODOLOGY (SSM) DI PPP PONDOKDADAP SENDANG BIRU, MALANG - Alvi Rahmah; Tri Wiji Nurani; Sugeng Hari Wisudo; Nimmi Zulbainarni (Jurnal Teknologi Perikanan dan Kelautan, 2013)
The aims of this study to formulate the problems of troll fisheries in Sendang Biru from the technical, ecological, and institutional aspects, in order to discover the conceptual model as a solution to the problems. Research was conducted in February 2013 in PPP Pondokdadap, using Soft Systems Methodology (SSM). The results showed that problems were the existence of competition for troll fisheries unit area, smaller size tuna were obtained, and weak institutional role in the monitoring and licensing of fishing. Therefore, there are 3 conceptual models into the initial solution that can be done by all parties concerned, namely (1) formulating the fishing operation of troll fisheries with FAD unit in PPP Pondokdadap, (2) developing and implementating of local regulation for monitoring, controlling, and survaillance of fishing ground in Southern water of Malang Regency, and (3) manufacturing and using of SOP licensing by local government.